A linguagem na literatura infantil: as várias falas do adulto para a criança - Ana Maria Clark Peres (1987)
Little Red Hood, the most widely known among the folklore tales, the so called "fairy tales", presents two classic adaptations which turned into landmarks for the several other versions: Perrault's (.France, late XVII century), presenting a tragic epilogue, and Grimm brothers' (Germany, early XIX century) showing a happy end. The analysis of thirt three Portuguese language versions of this tale pointed out significant alterations of both original structures. Important passages for the development of the narrative are omitted and/or irrelevant data are added in a style of expression almost always puerile and marked by cliche and didactism. These problems related to the text are accompanied, many times, by others concerning printing, revealing the disrespect and the belittlement towards the children in most of the cultural productions addressed to them.